The Impact of Video and Subtitle Speed on Subtitle Reading: An Eye-tracking Replication Study - Szarkowska, Agnieszka; Ragni, Valentina; Orrego-Carmona, David; Black, Sharon; Szkriba, Sonia; Kruger, Jan-Louis; Krejtz, Krzysztof; Silva, Breno (Journal of Audiovisual Translation, 2024)
We present results of a direct replication of Liao et al.’s (2021) study on how subtitle speed and the presence of concurrent video impact subtitle reading among British and Polish viewers. Our goal was to assess the generalisability of the original study’s findings on a cohort of Australian English. The study explored both subtitle-level and word-level effects, considering the presence or absence of concurrent video and three subtitle speeds: 12 characters per second, 20 cps, and 28 cps. Overall, most of the original results were replicated, confirming that the presence of video and the speed of the subtitles have a measurable impact on processing across different viewer groups. Additionally, differences in how native and non-native speakers process subtitles emerged, in particular related to wrap-up, word frequency and word length effects. The paper describes the replication in detail, presents the findings, and discusses some of their implications. Lay summary In our study we were interested in the effects that the presence of video and various subtitle speeds have on how viewers watch subtitled videos and how they understand them. We also wanted to know if the previous results obtained in a study by Liao et al. (2021) in Australia hold true for other viewers living in different locations. With this goal in mind, we repeated Liao et al.’s (2021) study on British and Polish viewers. The study explored both subtitle-level and word-level effects, considering the presence or absence of video and three subtitle speeds: 12 characters per second, 20 cps, and 28 cps. Overall, most of the original results were confirmed, showing that the presence of video and the speed of the subtitles have an impact on processing across different viewer groups. Additionally, differences in how native and non-native speakers process subtitles emerged, in particular related to well-known linguistic effects from reading studies, such as wrap-up, word frequency and word length effects. The paper describes the replication in detail, presents the findings, and discusses some of their implications.